Factors Affecting for Deposit Mobilization in Sri Lanka - Gunasekara, Helani Udara; Kumari, Prasansha (International Review of Management and Marketing, 2018)
Deposit mobilization is the process of public cash or funds accumulation by the financial institutes via its different routes, for instance, savings, current, fixed deposit accounts and other specialized schemes. The main objective of this study is to investigate the most effective factors affecting deposit mobilization, followed by a random sampling method, in which 120 deposit account holders were selected as a sample from three different convenient sample areas. The Questionnaires are equipped with questions to obtain primary data .The data has been analyzed using “Descriptive statistics” and “Regression analysis”. The study reveals that, there is a significant and positive relationship between deposit mobilization and deposit interest rate, security, branch expansion, services, technology and awareness. Moreover, there is a significant relationship between living area and the amount of deposits and the demographic variables, such as, gender, occupation, education level and income significantly affect for deposit mobilization. Keywords: Deposit Mobilization, Deposits, Banking sector, Financial System, Security, Technology and Awareness JEL Classifications: G2, G21 https://doi.org/10.32479/irmm.5887